Mengorganisasikan Pembelajaran Tema Cinta Lingkungan di Madrasah Ibtidaiyah - B. Siti Mardliyah; Irawan (Advances In Education Journal, 2025)
The challenges of global climate change and environmental degradation require the instilling of ecological awareness from an early age. Madrasah Ibtidaiyah (MI), as a primary educational institution, plays a crucial role in shaping environmentally conscious character. However, the limited availability of a comprehensive and integrated learning model often hinders the implementation of effective environmental education. Therefore, this study aims to describe effective strategies for organizing learning with an environmental theme at the Madrasah Ibtidaiyah (MI) level. The main problem is how to integrate environmental values into the curriculum and daily activities of MI in a holistic manner that is relevant to student development. This study uses a qualitative descriptive method with a literature review to develop a conceptual framework. The description of the findings indicates that organizing environmental learning in MI should be carried out through a thematic-integrative approach, involving problem-based projects (PBL) such as school waste banks or mini gardens, and emphasizing hands-on activities. Effective learning requires collaboration between teachers, students, parents, and the surrounding community.